2016
DOI: 10.1177/0263774x16666814
|View full text |Cite
|
Sign up to set email alerts
|

Are entrepreneurial and market orientations of small and medium-sized enterprises associated with targeting different tiers of public procurement?

Abstract: A general view is that small and medium-sized enterprises are underrepresented in public procurement due to their resource constraints. The recent literature suggests that small and medium-sized enterprises' strategic orientations could also have a role in the underrepresentation. In addition, small and medium-sized enterprises tend to position themselves either towards national or wider level public sector customers or towards sub-national level public sector customers. This paper studies how strategic orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 50 publications
2
24
0
1
Order By: Relevance
“…While such studies provide an insight into the practice–policy interface, they tend to be less grounded in theories, which would help to explain why smaller firms often find supplying public sector organizations challenging. A few exceptions to this approach were the recent works by Tammi et al () and Flynn and his colleagues (). Tammi, Reijonen, and Saastamoinen () showed that strategic orientation, namely entrepreneurial and market orientation, of the small and medium‐sized enterprises affect their targeting of different tier of the public sector market and its impact on their performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While such studies provide an insight into the practice–policy interface, they tend to be less grounded in theories, which would help to explain why smaller firms often find supplying public sector organizations challenging. A few exceptions to this approach were the recent works by Tammi et al () and Flynn and his colleagues (). Tammi, Reijonen, and Saastamoinen () showed that strategic orientation, namely entrepreneurial and market orientation, of the small and medium‐sized enterprises affect their targeting of different tier of the public sector market and its impact on their performance.…”
Section: Introductionmentioning
confidence: 99%
“…A few exceptions to this approach were the recent works by Tammi et al () and Flynn and his colleagues (). Tammi, Reijonen, and Saastamoinen () showed that strategic orientation, namely entrepreneurial and market orientation, of the small and medium‐sized enterprises affect their targeting of different tier of the public sector market and its impact on their performance. Flynn and Davis () used an institutional perspective to examine the extent to which the public sector buyers comply with the policy measures aimed at encouraging small and medium enterprises engagement in the public sector market.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Pickernell et al (2011) highlight a spatial aspect of innovation procurement by noting that the public-sector demand from non-local sources provides support for innovative firms. This is corroborated by Tammi et al (2017) who report that entrepreneurial SMEs tend to seek public sector contracts from non-local sources.…”
Section: Operational and Empirical Refinementsmentioning
confidence: 58%
“…Further, Pickernell et al (2011) highlight a spatial aspect of innovation procurement by noting that the public sector demand from non-local sources provides support for innovative firms. This is corroborated by Tammi et al (2016) who report that entrepreneurial SMEs tend to seek public sector contracts from non-local sources.…”
Section: Introductionmentioning
confidence: 58%